Analysis of the Application of the Joyful Learning Model to Improve Student Learning Outcomes in ISMUBA Lessons in Junior High School - Mar'atul Hidayah Izzatul Islami; Abd. Madjid (Universitas Muhammadiyah Mataram, 2026)
The learning of ISMUBA (Al-Islam, Muhammadiyahan, and Arabic) at Muhammadiyah Junior High School 1 Gamping plays an important role in shaping the religious understanding and character of students. However, learning practices in schools still face low enthusiasm and student involvement due to monotonous learning patterns and minimal participation. This condition encourages the need to implement a learning model that is able to create a fun and meaningful learning atmosphere. This study aims to analyze the application of the Joyful Learning model in improving student learning outcomes in ISMUBA subjects. The research uses a qualitative approach with a case study design through in-depth interviews. Data were analyzed using the Miles and Huberman interactive model, including data condensation, data display, and conclusion drawing. The credibility of the findings was enhanced through cross-informant comparison among the participating ISMUBA teachers. The results of the study show that Joyful Learning can increase student involvement through interactive activities, discussions, and the use of varied learning media, so that the understanding of ISMUBA material becomes more contextual. The implementation of this model is supported by curriculum flexibility, teacher creativity, and school support, although it still faces time constraints and differences in student character. These findings show that Joyful Learning is relevant to strengthen the quality of ISMUBA learning that is oriented towards meaningful learning and character development.